2009
DOI: 10.1186/1756-0500-2-19
|View full text |Cite
|
Sign up to set email alerts
|

IP-10, MCP-1, MCP-2, MCP-3, and IL-1RA hold promise as biomarkers for infection with M. tuberculosis in a whole blood based T-cell assay

Abstract: Background: IFN-γ responses to M. tuberculosis antigens are used as in-vitro diagnostic tests for tuberculosis infection. The tests are highly specific but sensitivity may be impaired due to immunosuppression. The objective of this small exploratory study was to compare three novel biomarkers for in-vitro diagnosis of tuberculosis -MCP-1, MCP-3 and IL-1RA -with the current established biomarker IFN-γ and the newly described IP-10 and MCP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 21 publications
(27 reference statements)
9
68
2
Order By: Relevance
“…A number of studies have previously highlighted the diagnostic potential of IP-10 (CXCL10). [24][25][26][27][28][29][30] In agreement with our findings, those studies showed that MTBspecific IP-10 responses in TB-infected individuals are of greater magnitude than IFN-γ responses, and that this biomarker lacks the ability to distinguish between LTBI and active TB. [24][25][26][27][28] This is not surprising as IP-10 production in polymorphonuclear neutrophils and monocytes is primarily induced by IFN-γ that also lacks this discriminatory ability (as reflected by IGRA lacking this ability).…”
Section: Receiver Operating Characteristic Analysessupporting
confidence: 80%
See 1 more Smart Citation
“…A number of studies have previously highlighted the diagnostic potential of IP-10 (CXCL10). [24][25][26][27][28][29][30] In agreement with our findings, those studies showed that MTBspecific IP-10 responses in TB-infected individuals are of greater magnitude than IFN-γ responses, and that this biomarker lacks the ability to distinguish between LTBI and active TB. [24][25][26][27][28] This is not surprising as IP-10 production in polymorphonuclear neutrophils and monocytes is primarily induced by IFN-γ that also lacks this discriminatory ability (as reflected by IGRA lacking this ability).…”
Section: Receiver Operating Characteristic Analysessupporting
confidence: 80%
“…52,53 The main limitation of this study is the inclusion of a limited number of patients with active TB, a limitation shared by many other studies in this area. 23,26,27,29,34,38 detection of statistical differences between the diagnostic groups. An important strength of this study is the use of unambiguous diagnostic groups in the analyses.…”
Section: Receiver Operating Characteristic Analysesmentioning
confidence: 99%
“…Consequently, novel concepts have been investigated that include the use of different epitopes of RD antigens [11,12,36,37,58], readout different from IFN-c such as chemokines or cytokines [56,58], new antigens different from the RD genomic region, such as those defined as Rv1733c, Rv2029c, Rv2032, Rv2626c, Rv2627c, Rv2628 and HspX [29,[59][60][61], additional cytokines [56] or characteristic phenotypic markers [11,12,36,62]. Diagnostic sensitivity of IGRA can also be enhanced by incorporation of a novel RD1-encoded antigen, Rv3879c, without compromising diagnostic specificity [63].…”
Section: Sectionmentioning
confidence: 99%
“…The diagnostic potential of IP-10 (125) also has been evaluated, with mixed results (54,149,167). Since secretion of IP-10 is less affected than that of IFN-␥ by immunosuppression (55) and is age independent (85), IP-10 has been proposed as an adjunct marker of LTBI diagnosis in pediatric and HIV-coinfected populations (85,124). In other studies, the levels of epidermal growth factor (EGF), sCD40L, vascular endothelial growth factor (VEGF), TGF-␣, and IL-1␣ released by antigen-stimulated PBMCs in a commercial IGRA distinguished TB patients from household contacts more accurately than any single marker alone (19).…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 99%